Best practices for your website Making your website work - for your user - Peabody, Melissa; Braddy, Holly; Stanford Video (California : Stanford Video [productions] ; Kantola Productions [distributors], 2003)
Discusses about website design from the visitor's perspective. Micheal Gold details specific suggestions to help you make your website work-for your user
Graphic, Paul Stelhe
Presented Micheal Gold ; narrator, Richard Gephardt
Keywords: Websites -- Design; Web publishing; World Wide Web (Information retrieval systems) -- Design